The Effect of Providing Psychoeducation on Stress Levels of Patients with Type II Diabetes Mellitus - Fatmawati; Haryanti Haris; Jusniati (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2023)
Psychoeducation is an action that is given to individuals and families as a way to deal with difficulties in mental changes through the provision of information related to simple psychology or other information that affects people's welfare. This study aims to determine the effect of psychoeducation on the stress level of type II DM patients in the Working Area of ​​the Caile Public Health Center, Bulukumba Regency. This type of research is a type of quantitative research. The design of this study used the